2023
DOI: 10.1007/s10854-022-09412-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical and opto-electrical study of Cr-doped-ZnO-based polyvinyl chloride nanocomposites

Abstract: Polymer nanocomposites exhibit unique physical properties inaccessible from their individual constituents, which are tunable through the type of the polymer matrix, the type and size of the incorporated nanoparticles, and the doping level, and therefore, can be utilized in a wide range of potential applications. Here, we report the fabrication of pure Polyvinyl chloride (PVC) and PVC-based nanocomposites containing different loadings of pure and Cr-doped ZnO nanoparticles, using solvent casting method. Scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…In addition, the absorption band of the doped polymer is redshifted relative to the undoped polymer, and this shift increased as the nanofiller preparation temperature is reduced, as shown in Figure 5a. The PVC loaded with Cr-doped ZnO exhibited a similar feature [12]. In the doped polymers, a new molecular bond between cations and anions may be responsible for this change.…”
Section: Optical Featuresmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, the absorption band of the doped polymer is redshifted relative to the undoped polymer, and this shift increased as the nanofiller preparation temperature is reduced, as shown in Figure 5a. The PVC loaded with Cr-doped ZnO exhibited a similar feature [12]. In the doped polymers, a new molecular bond between cations and anions may be responsible for this change.…”
Section: Optical Featuresmentioning
confidence: 74%
“…Tin-doped ZnS@ polyvinyl pyrrolidine polymeric composite films with altered photoluminescent and electrical properties were developed by Badawi et al for use in light-emitting diodes [11]. The preservation of the optical properties of the incorporated nanoparticles makes these nanocomposites promising candidates for optoelectronic devices, and the thermomechanical stability of the Cr-doped ZnO-based PVC nanocomposite samples may alter the traditional roles of PVC polymers from insulators to those of materials for energy storage and capacitors [12]. PVC-doped iodine thin films' optical, chemical, and thermal properties can be modified by incorporating an appropriate concentration of iodine nanofiller into the PVC polymeric matrix [13].…”
Section: Introductionmentioning
confidence: 99%
“…The real value of dielectric permittivity is proportional to the number of oriented dipoles present in the tested material and their capacity to undergo orientation at the applied frequency. When the frequency rises, there will not be sufficient time for dipoles to follow the applied field and contribute to the orientation polarization, resulting in a decrease in ε′ rates [57][58][59]. However, the irregular increase in relative permittivity values in the megahertz range is attributed to the possible resonance effects resulting from insufficient contact in the measuring cell [60,61].…”
Section: Permittivity and Dielectric Lossmentioning
confidence: 99%
“…Over the years, numerous scholars have found that the addition of inorganic particles to composites can effectively increase the breakdown field strength, suppress space charge, and even modulate carrier flow [9][10][11][12][13]. This method of improving certain physical and chemical properties by adding inorganic particles is widely used in industry and engineering.…”
Section: Introductionmentioning
confidence: 99%